2014
DOI: 10.6001/biologija.v60i1.2863
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Borrelia burgdorferi sensu lato in questing Ixodes ricinus ticks in Norway

Abstract: Norway represents the northern limit in the geographical distribution of Ixodes ricinus ticks in Europe. During the last decade an expansion of the range of this tick further north and at higher altitudes has been detected. This could affect the spread of Borre lia burgdorferi sensu lato pathogens in new territories and increase the risk of human infection in the country. The aim of the present study was to determine the prevalence of B. burgdorferi s.l. in I. ricinus ticks in different localities of Norway. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cisak et al (2006) revealed that 16.8% of the Borrelia-positive samples were coinfected with two spirochete genospecies, whereas triple infections occurred in 1.8% of tick specimens gathered at woody habitats in Lublin region (eastern part of Poland). Stańczak et al (2000) (Rosef et al 2014). Moreover, Lommano et al (2012) revealed that polymicrobial infections with two or three spirochete genospecies were identified in 2.1% ticks gathered in western Switzerland, and further observation revealed that coexistence of B. garinii and B. valaisiana was most frequent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cisak et al (2006) revealed that 16.8% of the Borrelia-positive samples were coinfected with two spirochete genospecies, whereas triple infections occurred in 1.8% of tick specimens gathered at woody habitats in Lublin region (eastern part of Poland). Stańczak et al (2000) (Rosef et al 2014). Moreover, Lommano et al (2012) revealed that polymicrobial infections with two or three spirochete genospecies were identified in 2.1% ticks gathered in western Switzerland, and further observation revealed that coexistence of B. garinii and B. valaisiana was most frequent.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that genetic variability of spirochete genotypes implies specific symptomatology of the borreliosis (Schwarz et al 2012). Furthermore, it was demonstrated that B. afzelii was predominantly associated with erythrema migrans, while B. garinii was mainly isolated from cerebrospinal fluid (CSF) that indicates its involvement with Lyme neuroborreliosis (LNB) (Rosef et al 2014).…”
Section: Introductionmentioning
confidence: 99%